Physico-chemical Properties of Fresh and Stored Meat as Influenced by Dietary Supplementation of Soy Acid Oil and Crude Soy Lecithin Alone or in Combination in Vencobb Broiler Chicken - Danipreetha, S.; Dubey, Meenu; Tiwari, S. P.; Dutta, G. K.; Pandey, Abhishek (Indian Journal of Animal Nutrition, 2017)
Day-old Vencobb broiler chicks (n= 288) were allocated to 6 dietary groups with 4 replicates of 12 birds in each. T1 was control, T2 and T3 contained 3% crude soy lecithin (CSL) and 2.5% soy acid oil (SAO) respectively, T4 to T6 contained both CSL and SAO (level 3%) in different combinations (75: 25, 50: 50 and 25:75,respectively). The diets were isocaloric and isonitrogenous. The mean pH value of fresh meat samples in control was higher (P